Comparing intravenous clonidine and nalbuphine for attenuating hemodynamic response to laryngoscopy and improving perioperative outcomes in laparoscopic surgeries - Kiwi Mantan; Neha Chahar; Sandeep Kothari; Rakesh; Gaurav Joshi (Journal of Applied Pharmaceutical Research, 2023)
The Department of Anaesthesia at SPMC Bikaner approved the trial and it was carried out during laparoscopic surgery OT with proper informed written permission. The study was a double-blind, randomised, prospective interventional trial. The study comprised 60 (ASA) Classes I and II patients between the ages of 18 and 60 who were scheduled for elective laparoscopic cholecystectomy. Using a computer-generated random number sequence, patients were divided into two groups of 30 each: Group A received 1.5 mg/kg of clonidine, whereas Group B received.2 mg/kg of nalbuphine in a 50 ml NS solution. Prior to administering the study drug, five minutes after premedication, hemodynamic parameters were recorded. Double-blind administration of the study medication occurred more than 10 minutes before anaesthesia onset. Hemodynamic parameters were recorded following the administration of the study medication, 1 and 5 minutes after intubation, prior to pneumoperitoneum, 5 minutes, 10 minutes, 20 minutes, 30 minutes, and 40 minutes after pneumoperitoneum, and finally following extubation. following 1 minute and 5 minutes after intubation (and following pneumoperitoneum at 5 minutes, 10 minutes, 20 minutes, and post extubation), it was discovered that there was a substantial difference in heart rate, SBP, DBP, and MAP between Group A and Group B. In our investigation, hemodynamics related to heart rate were improved with clonidine. Based on the results of our study and other earlier research conducted by different authors, we came to the conclusion that both clonidine and nalbuphine, when administered 5 minutes prior to intubation in patients undergoing laparoscopic surgery, attenuated the hemodynamic response to intubation and pneumoperitoneum during the surgery. The difference in heart rate, systolic and diastolic blood pressure, and mean arterial pressure is much less with clonidine than with nalbuphine, which leads us to the conclusion that clonidine produced greater hemodynamic response than nalbuphine.